2013
DOI: 10.2190/hs.43.4.i
|View full text |Cite
|
Sign up to set email alerts
|

Africanizing the Social Determinants of Health: Embedded Structural Inequalities and Current Health Outcomes in Sub-Saharan Africa

Abstract: There is a growing interest in health policy in the social determinants of health. This has increased the demand for a paradigm shift within the discipline of health economics from health care economics to health economics. While the former involves what is essentially a medical model that emphasizes the maximization of individual health outcomes and considers the social organization of the health system as merely instrumental, the latter emphasizes that health and its distribution result from political, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…From studies on socioeconomic inequalities in health, we know that poor and vulnerable populations may bear a greater burden of COVID-19 in the long term [26,27]. However, the full economic impact of COVID-19 on the economies of countries in Africa cannot be ascertained at the moment as the situation unfolds.…”
Section: Resultsmentioning
confidence: 99%
“…From studies on socioeconomic inequalities in health, we know that poor and vulnerable populations may bear a greater burden of COVID-19 in the long term [26,27]. However, the full economic impact of COVID-19 on the economies of countries in Africa cannot be ascertained at the moment as the situation unfolds.…”
Section: Resultsmentioning
confidence: 99%
“…Addressing the SDH is essential for reducing health inequalities [7,[21][22][23][24][25][26], especially in developing countries with weak health systems. Thus, we argue that the COVID-19 outbreak that is compounding morbidity and mortality has put a spotlight on the SDH as central for improving population health in developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal studies from developed countries have found a causal relationship between socioeconomic position and ADL [ 66 ]. However, measures of socioeconomic status may not necessarily be interpreted the same way in the African context [ 67 ]. Therefore, longitudinal studies set in sub-Saharan Africa are needed to elucidate the association between financial dependency and functional status among the elderly.…”
Section: Discussionmentioning
confidence: 99%